Insight into the Molecular Mechanism of the Transcriptional Regulation of amtB Operon in Streptomyces coelicolor - Li, Zhendong; Liu, Xinqiang; Wang, Jingzhi; Wang, Ying; Zheng, Guosong; Lu, Yinhua; Zhao, Guoping; Wang, Jin (Frontiers in Microbiology, 2018)
In Streptomyces coelicolor, amtB transcription is promptly regulated by the global nitrogen regulator GlnR. Although the GlnR binding cis-element has been characterized in amtB promoter, consisting of three GlnR boxes of a3-b3, a1-b1 and a2-b2, its role in GlnR-mediated transcriptional regulation remains unclear. Here, we showed that GlnR had different binding affinity against each pair of GlnR binding sites in amtB promoter (i.e., a3-b3, a1-b1 and a2-b2 sites), and GlnR was able to bind a3-b3 and a1-b1, respectively, but not a2-b2 alone. Consistently, a2 was not a typical GlnR binding site and further experiments showed that a2 was non-essential for GlnR-mediated binding in vitro and transcriptional regulation in vivo. To uncover the physiological role of the three GlnR boxes, we then mutated the wild-type amtB promoter to a typical GlnR-binding motif containing two GlnR boxes (a3-b3-a2-b2), and found although the transcription of the mutated promoter could still be activated by GlnR, its increasing rate was less than that of the wild type. Based on these findings, one could conclude that the three GlnR boxes assisted GlnR in more promptly activating amtB transcription in response to nitrogen limitation, facilitating bacterial growth under nitrogen stresses.